A JURIDICAL STUDY OF REGIONAL REGULATION NO. 4 OF 2008 CONCERNING HOW MEDAN CITY'S GOVERNMENT CONTROLS VAGRANTS AND BEGGARS - Darma, Mospa; Na'im, Khairun (Universitas Ekasakti, 2023)
Homelessness and begging is a social phenomenon that must be taken seriously. This phenomenon is becoming more and more concerning. Although the government has always tried to reduce the population of vagrants and beggars through curbing operations, the number of vagrants and beggars never seems to decrease and even tends to increase. This study aims to describe the problems that occur in homeless people and beggars. This study is conducted research what is qualitative as well as descriptive that aims to describe the existing phenomena connected to the problem of homeless and Medan City's beggars. Documentation, observation, and interviews are the data gathering techniques used. The findings of this study indicate that the factors that lead to vagrant and beggar are limited employment opportunities, low levels of education, economic living conditions and mental factors, lack of parental attention, promiscuity, laziness to work, environmental influences, disability. As for the obstacles faced by the government in handling vagrants and beggars in Medan City, there are internal factors and external factors.